Building Customer Satisfaction Through CABOX Photobox Employee Service Communication - Samantha Sumaraw; Yenny; Nur’annafi (PT FORMOSA CENDEKIA GLOBAL, 2026)
In an era of increasingly fierce business competition, service companies are required not only to offer high-quality products or services but also to provide a satisfying service experience for customers. This study aims to explain the relationship between employee service communication and customer satisfaction at Photobox CABOX. The study employs a qualitative method with a descriptive approach. The research subjects were Photobox CABOX customers who had used the photobox service and interacted directly with employees during the service process. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that customer satisfaction at Photobox CABOX is shaped by employee service communication that prioritizes clarity of information, empathy, responsiveness, friendliness, and equal treatment of all customers.